2002
DOI: 10.1007/bf02492470
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrophoretic separation of sulphonated anthraquinones in a variety of matrices

Abstract: SummarySulphonated anthraquinones are resistant to biodegradation and are, therefore, not eliminated by traditional wastewater treatment plants; this leads to their accumulation in fresh water. To develop new technologies, e.g. phytoremediation, for treatment of such pollutants, a powerful technique is needed for their rapid and inexpensive detection and quantification in any kind of sample. For this purpose capillary electrophoresis seems to be a very promising technique.An efficient, rapid, and inexpensive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Indeed, quinones play a substantial role in the processes of storage and conversion of chemical energy, such as photosynthesis and the oxidative phosphorylation. 11 Polar quinones, among which are the derivatives of anthraquinonesulfonic acid, are present in water 12 while the apolar specimens are often detected in atmospheric particulate matter. 13 These environmentally widespread compounds are also photochemically active, [14][15][16][17] and their photoactivity is often linked with the absorption band at the longest wavelengths (usually in the near-UV to visible region).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, quinones play a substantial role in the processes of storage and conversion of chemical energy, such as photosynthesis and the oxidative phosphorylation. 11 Polar quinones, among which are the derivatives of anthraquinonesulfonic acid, are present in water 12 while the apolar specimens are often detected in atmospheric particulate matter. 13 These environmentally widespread compounds are also photochemically active, [14][15][16][17] and their photoactivity is often linked with the absorption band at the longest wavelengths (usually in the near-UV to visible region).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these results might also indicate that both xenobiotic compounds were transported from the roots to the shoot. Aubert and Schwitzguébel (2002) have shown that some sulphonated anthraquinones are found in the leaves of rhubarb and common sorrel after an exposure of 6 weeks to these compounds. When AQ-1, 5-SS and AQ-1,8-SS were used as substrates, an activity of cytochromes P450 was detected only in the exposed roots of rhubarb (AQ-1,5-SS) and celery (both AQs).…”
Section: Discussionmentioning
confidence: 99%
“…The next step has thus been to investigate any possible adsorption, uptake, metabolism and degradation by the plant and its different organs. As measured by capillary electrophoresis, several sulphonated anthraquinones and different metabolites, not yet characterised, have been found in leaves of rhubarb and R. hydrolapatum, suggesting that these plant species are able to accumulate and metabolise these compounds (Aubert and Schwitzguébel 2002;Aubert 2003;Schwitzguébel et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Sulphonated anthroquinones dyes are resistant to biodegradation and an efficient, rapid, and inexpensive CE method using a borate buffer has been developed [53] for analysis of five sulphonated anthraquinones, in the range 50-950 M, with a simple borate buffer. The method has been used to measure environmental levels and assess a variety of wastewater treatment approaches.…”
Section: Environmental Monitoring Applicationsmentioning
confidence: 99%